Prospect of Castor Oil Biodiesel in Bangladesh: Process Development and Optimization Study - Deb, Anjan; Ferdous, Jannatul; Ferdous, Kaniz; Uddin, M. Rakib; Khan, Maksudur R.; Rahman, Md. Wasikur (Taylor & Francis, 2017)
In this study, Castor oil (CO) has been investigated as a potential source for biodiesel production in Bangladesh. Castor oil has been extracted from the seeds by mechanical press and Soxhlet extraction method. Maximum oil content of 55.7% has been found by Soxhlet extraction method. The physicochemical properties such as free fatty acid (FFA) content, kinematic viscosity, saponification value and density of the oil have been measured by different standard methods. The FFA content and viscosity has been found considerably higher such as 33.5% and 253 mm²/s respectively. Biodiesel has been prepared using a three-step method comprises with saponification of oil followed by acidification of the soap and esterification of FFA. The overall yield of FFA from CO is found to be around 89.2%. The final step is esterification that produces fatty acid methyl ester (FAME) and a maximum 97.4% conversion of FFA to biodiesel has been observed. The effect of oil to methanol molar ratio, catalyst concentration, reaction temperature and time has been investigated for esterification reaction and optimized using response surface methodology. 1H NMR of crude castor oil and castor oil methyl ester (COME) was studied and analyzed that confirms the complete conversion of castor oil to biodiesel. Finally, the biodiesel, produced at optimum condition, was characterized under various standard method and found comparable with petro-diesel and biodiesel standard.